A Soft Approach To Channel Conflicts: Enhancing Dual Distribution Channel Coordination In B2B Markets - Budiaji, Lukman; Novani, Santi (JRB-Jurnal Riset Bisnis, 2023)
Effective decision-making regarding distribution channels is crucial for organizations, as the relationships between manufacturers and intermediaries usually involve long-term commitments that are difficult to change. However, organizations must be prepared to adapt their distribution practices to grow their businesses in uncertain and highly competitive markets. One common approach in the B2B market is the dual distribution channel, which integrates manufacturer-owned distributors and independent distributors to respond to a variety of customer needs and increase revenue. Conflicts between these two channels have resulted in trust breakdowns, high resistance to coordination, and unaccomplished revenue goals. To address these issues, the paper proposes soft system methodology (SSM) as a change process approach to improve the dual distribution system and channel coordination to increase revenue and stay ahead of the competition. The proposed change action using SSM involves engaging stakeholders and actively involving them in decision-making to create a sense of ownership of the change process. To facilitate this process, the paper adopts the 7-S framework from McKinsey as an auxiliary tool to identify relevant issues, worldviews, and required transformations in a time-constrained situation.